2020
DOI: 10.1155/2020/8814136
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Swine Gastrointestinal Parasites in Nyagatare District, Rwanda

Abstract: While pig farming has been growing rapidly in Rwanda, its potential contribution to the prevalence of zoonotic infections is not well known. Pig production is usually affected by gastrointestinal parasites, some of which are zoonotic and can threaten human health. The knowledge about the status of such infections is essential for policy decisions and interventions. We aimed to investigate the prevalence of swine gastrointestinal parasites in Nyagatare district, Rwanda. A cross-sectional study involved collecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
2
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 22 publications
0
9
2
1
Order By: Relevance
“…The results of the current study, which show an overall prevalence of 63% for nematodes, are in close proximity with the findings of Boes et al (2000) in China, who reported 58% of nematodes. The current results are however below 72%, which was reported by Tumusiime et al (2020) in Rwanda.…”
Section: Resultscontrasting
confidence: 91%
See 1 more Smart Citation
“…The results of the current study, which show an overall prevalence of 63% for nematodes, are in close proximity with the findings of Boes et al (2000) in China, who reported 58% of nematodes. The current results are however below 72%, which was reported by Tumusiime et al (2020) in Rwanda.…”
Section: Resultscontrasting
confidence: 91%
“…This rate of prevalence is, however, lower than the 40.7% and 47.2% reported by Roesel et al (2017) and Weng et al (2005) in Uganda and China, respectively. According to Tumusiime et al (2020), the disparities between different studies can be explained by variations in production systems. The current results provide ample evidence that nematodes represent the major health threat in the study area and this call for the attention of pig producers to revive their de-worming programs in such a way that it targets the nematodes.…”
Section: Resultsmentioning
confidence: 99%
“…Lower intestinal parasite infection rates than those in this study have been detected in pig feces from farms located in other municipalities in Brazil, such as in the semi-confined production system in Mossoró, Rio Grande do Norte and in Pinheral, Rio de Janeiro, in which 72.7% and 30% of positivity rates, respectively, were found, as well as at family farms in Paraíba (79.5%), Rio Grande do Sul (43.2%) and Minas Gerais (62.9%) [18][19][20][21][22]. Case records of parasite infections in pigs lower than those in this study, varying from 13.2% to 84.6%, have also been reported on family farms in other countries, including Peru, Venezuela, Ethiopia, Uganda, Rwanda and India [16,[23][24][25][26][27].…”
Section: Discussionmentioning
confidence: 55%
“…The helminths in this category include Strongyle-type species ( Oesophagotomum spp., Hyostrongylus rubidus ), Strongyloides spp., Ascaris spp., Trichuris spp., and Fasciolopsis spp. [ 9 ]. GI parasistes are a significant contributor to economic losses in pig farming.…”
Section: Introductionmentioning
confidence: 99%